Faktor – Faktor Yang Berhubungan Dengan Kejadian IKTERUS Pada Neonatus di TPMB Hj. Leli Murni Kota Makassar - Ahmad, Amina (Jurnal Ilmiah Amanah Akademika, 2019)
Based on the data of SDKI in 2012 The incidence of jaundice in newborns ranges from 50% in term infants and 75% in underweight infants. This study aims to determine the factors associated with the incidence of Ikterus in Neonates. This type of quantitative research through the design of analytical research with cross sectional approach. Population of this study all neonates born 0-28 days life as 1041 neonates, large sample 196 neonatus, sample technique used systematic random sampling. Data analysis using univariate, bivariate, and multivariate. The result of chi square test showed a correlation between neonatal jaundice with birth weight (p- value 0,000 <0,05), OR = 3.084, gestation period (p-value 0,000 <0.05), OR = 4,721, infection (p-value 0.005<0.05), OR = 2.444, asphyxia (p-value 0.015 <0.05), OR = 2.181 there is no relation type of labor (p-value 0.607> 0.05), OR = 0.821 with the occurrence of jaundice. the results of multiple logistic regression test obtained variable gestation most dominant related to the incidence of jaundice in neonates (p-value 0.000), OR = 4.698, PUS is expected to checkups at least 4 visits, to pregnant women can maintain her personal hygiene especially vulva hygiene to prevent the occurrence of infection